2017
DOI: 10.1016/j.jjcc.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of vasa vasorum neovascularization using intravascular ultrasound: A comparison between acute coronary syndrome and stable angina pectoris

Abstract: VV neovascularization of coronary arteries was more enhanced in patients with ACS than in those with SAP, supporting its relation to plaque vulnerability. VV detected by widely used IVUS could be an adequate surrogate marker for plaque vulnerability in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Recently, imaging of the vasa vasorum in the clinical setting has been receiving considerable attention. In this study, Kume et al [4] demonstrated the potential of gray-scale IVUS for detecting adventitial vasa vasorum in coronary arteries. As the result of this study shows, the gray-scale IVUS-detected vasa vasorum density might serve as a new surrogate marker for plaque vulnerability.…”
Section: Final Remarksmentioning
confidence: 64%
See 2 more Smart Citations
“…Recently, imaging of the vasa vasorum in the clinical setting has been receiving considerable attention. In this study, Kume et al [4] demonstrated the potential of gray-scale IVUS for detecting adventitial vasa vasorum in coronary arteries. As the result of this study shows, the gray-scale IVUS-detected vasa vasorum density might serve as a new surrogate marker for plaque vulnerability.…”
Section: Final Remarksmentioning
confidence: 64%
“…), plaque progression or regression, and clinical events. This study by Kume et al [4] will form a basis of those future researches with gray-scale IVUS for investigating the role of vasa vasorum in coronary atherosclerosis.…”
Section: Final Remarksmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on their histological validation study, Kume et al demonstrated with a commercially-available IVUS that the prevalence of the VV at the proximal and distal reference segments adjacent to culprit lesions was significantly increased in patients with acute coronary syndrome compared with those with stable angina pectoris. 12,14 Using commercially-available echogenic microbubbles composed of albumin microspheres filled with octafluoropropane gas, Vavuranakis et al demonstrated the feasibility of the IVUS contrast-enhancement detection techniques for the VV in both the adventitia and the plaque of human coronary arteries in vivo. 15…”
Section: Clinical Relevancementioning
confidence: 99%
“…However, the lack of adequate noninvasive and high-resolution imaging technology to visualize VV is a big challenge. Micro-CT, optical coherent tomography (OCT), intravascular ultrasound (IVUS) angiography and contrast-enhanced ultrasound (CEU) imaging have been demonstrated to image VV in pre-clinical studies, but these technologies have suffered from hazardous radiation (micro-CT), poor imaging depth (OCT), invasive approach (IVUS) and insufficient spatial resolution (CEU) 5 , 6 , 11 16 .…”
Section: Introductionmentioning
confidence: 99%